Genomic and microbiological analyses of iron acquisition pathways among respiratory and environmental nontuberculous mycobacteria from Hawai’i - Tan, Cara G.; Oberlag, Nicole M.; McGowan, Acelyn E.; Dawrs, Stephanie N.; Chan, Yvonne L.; Strong, Michael; Hasan, Nabeeh A.; Honda, Jennifer R. (Frontiers in Microbiology, 2023)
As environmental opportunistic pathogens, nontuberculous mycobacteria (NTM) can cause severe and difficult to treat pulmonary disease. In the United States, Hawai’i has the highest prevalence of infection. Rapid growing mycobacteria (RGM) such as Mycobacterium abscessus and M. porcinum and the slow growing mycobacteria (SGM) including M. intracellulare subspecies chimaera are common environmental NTM species and subspecies in Hawai’i. Although iron acquisition is an essential process of many microorganisms, iron acquisition via siderophores among the NTM is not well-characterized. In this study, we apply genomic and microbiological methodologies to better understand iron acquisition via siderophores for environmental and respiratory isolates of M. abscessus, M. porcinum, and M. intracellulare subspecies chimaera from Hawai’i. Siderophore synthesis and transport genes, including mycobactin (mbt), mmpL/S, and esx-3 were compared among 47 reference isolates, 29 respiratory isolates, and 23 environmental Hawai’i isolates. Among all reference isolates examined, respiratory isolates showed significantly more siderophore pertinent genes compared to environmental isolates. Among the Hawai’i isolates, RGM M. abscessus and M. porcinum had significantly less esx-3 and mbt genes compared to SGM M. chimaera when stratified by growth classification. However, no significant differences were observed between the species when grown on low iron culture agar or siderophore production by the chrome azurol S (CAS) assay in vitro. These results indicate the complex mechanisms involved in iron sequestration and siderophore activity among diverse NTM species.